Oxide solid electrolyte, electrode mixture, and all-solid-state lithium-ion battery
Patent Information
- Application Number
- JP2021002328
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-08
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2041-01-08
AI Technical Summary
【0011】 本開示の上記態様によれば、常温での良好な変形性を有し、かつ、導電率が高い酸化物固体電解質、電極合材および全固体リチウムイオン電池を提供することができる。
Smart Images

Figure 0007634256000006 
Figure 0007634256000001 
Figure 0007634256000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an oxide solid electrolyte, an electrode mixture, and an all-solid-state lithium ion battery. [Background technology]
[0002] Lithium-ion secondary batteries have a high energy density and are used in information-related devices such as personal computers and mobile phones. In recent years, development of high-output, high-capacity lithium-ion secondary batteries for electric or hybrid vehicles has been progressing.
[0003] However, current lithium-ion secondary batteries use flammable organic electrolytes, which means that they are prone to catching fire when they generate abnormal heat. In fact, there have been fires caused by lithium-ion secondary batteries in portable devices, and there is a strong demand for safety improvements.
[0004] One of the technologies to improve the safety of lithium-ion secondary batteries is the use of solid electrolytes. However, in the case of all-solid-state lithium-ion secondary batteries using solid electrolytes, the negative electrode composite layer, the solid electrolyte layer, and the positive electrode composite layer are in solid-solid contact. Therefore, compared to conventional lithium-ion secondary batteries using organic electrolytes, the number of paths for electron and ion movement is significantly reduced. In particular, oxide solid electrolytes with high electrical conductivity are hard particles that are difficult to deform, so good solid-solid contact cannot be obtained even by pressing. Therefore, in oxide solid electrolytes with high electrical conductivity, the conductivity of electrons or ions between oxide solid electrolytes is low. Therefore, there is currently a demand to improve the contact state between solid electrolytes.
[0005] As a technique for improving the contact state between solid electrolytes, Patent Document 1 discloses a technique for sintering a lithium ion conductive inorganic material containing 2.6 to 52.0% of ZrO2 component in mass % based on oxide. Non-Patent Document 1 discloses a technique for sintering glass ceramics having a NASICON type crystal structure. Non-Patent Document 2 discloses a technique for hot pressing Li3BO3-Li2SO4. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2012-246196 A [Non-patent literature]
[0007] [Non-Patent Document 1] T. Kato, et al.,Effects of sintering temperature on interfacial structure and interfacial resistance for all-solid-state rechargeable lithium batteries. J. Power Source 325(2016)584-590 [Non-Patent Document 2] K. Nagao,et al., Highly Stable Li / Li3BO3-Li2SO4 Interface and Application to Bulk-Type All-Solid-State Lithium Metal Batteries. Appl. Energy Mater. 2(2019) 3042-3048 Summary of the Invention [Problem to be solved by the invention]
[0008] In the case of Patent Document 1 and Non-Patent Document 1, the contact between particles is improved by sintering at high temperature, but there is a problem that the ion conductivity and charge / discharge reactivity are reduced due to the reaction of the solid electrolyte and the electrode active material at high temperature. In addition, in the case of Patent Document 1 and Non-Patent Document 1, since processing at high temperature is required, there is a problem that the equipment cost and running cost are high. In addition, in the technology of Non-Patent Document 2, the contact state between particles is improved by hot pressing a material that does not form a good interparticle contact state at room temperature, but since a high temperature is required, there is a problem that the equipment cost and running cost are high. Therefore, a solid electrolyte having higher deformability at room temperature than the solid electrolyte disclosed in Non-Patent Document 2 is required.
[0009] The present invention has been made in consideration of the above problems, and has as its main object to provide an oxide solid electrolyte having good deformability at room temperature and high electrical conductivity. Here, room temperature refers to 20° C. to 30° C. In addition, "good deformability at room temperature" refers to, for example, deformability in which the relative density is 95% or more when pressed at room temperature and 1 GPa. [Means for solving the problem]
[0010] In order to solve the above problems, the present invention proposes the following means. (1) An oxide solid electrolyte according to one embodiment of the present invention is a composite containing lithium sulfate (Li2SO4) and lithium carbonate (Li2CO3), the molar ratio of the lithium sulfate to the lithium carbonate (Li2SO4:Li2CO3) is 20:80 to 80:20; In the curve obtained by differential scanning calorimetry, the position of the exothermic peak is 190 °C or less, and the conductivity is 1.0 x 10 -7 S / cm or more. (2) The oxide solid electrolyte described in (1) above may further contain at least one selected from the group consisting of lithium chloride, lithium bromide, lithium iodide, lithium borate, lithium phosphate, lithium nitrate, lithium silicate, and lithium aluminate. (3) An electrode mixture according to one embodiment of the present invention comprises: The oxide solid electrolyte according to (1) or (2) above, An electrode active material; A conductive material; Including, The mass ratio of the oxide solid electrolyte, the electrode active material, and the conductive material (oxide solid electrolyte:electrode active material:conductive material) is 20-80:20-80:0-30. (4) An all-solid-state lithium-ion battery according to an embodiment of the present invention includes the oxide solid electrolyte described in (1) or (2) above. (5) The all-solid-state lithium ion battery described in (4) above may include a solid electrolyte layer containing the oxide solid electrolyte. (6) The all-solid-state lithium ion battery according to (4) or (5) above may include a positive electrode active material layer containing the oxide solid electrolyte or a negative electrode active material layer containing the oxide solid electrolyte. (7) The all-solid-state lithium-ion battery according to (6) above, wherein the positive electrode active material layer contains the oxide solid electrolyte, a positive electrode active material, and a positive electrode conductive material, The mass ratio of the oxide solid electrolyte, the positive electrode active material, and the positive electrode conductive material (oxide solid electrolyte: positive electrode active material: positive electrode conductive material) may be 20-80:20-80:0-30. (8) The all-solid-state lithium-ion battery according to (6) or (7) above, wherein the negative electrode active material layer contains the oxide solid electrolyte, a negative electrode active material, and a negative electrode conductive material, The mass ratio of the oxide solid electrolyte, the negative electrode active material, and the negative electrode conductive material (oxide solid electrolyte:negative electrode active material:negative electrode conductive material) may be 20-80:20-80:0-30. Effect of the Invention
[0011] According to the above-described aspects of the present disclosure, it is possible to provide an oxide solid electrolyte, an electrode mixture, and an all-solid-state lithium ion battery that have good deformability at room temperature and high electrical conductivity. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a schematic cross-sectional view of an all-solid-state lithium-ion battery according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] <Oxide solid electrolyte> The oxide solid electrolyte of the present disclosure will be described. Note that the following exemplary embodiments are provided to facilitate understanding of the present invention and are not intended to limit the present invention. The present invention can be modified or improved from the following embodiments without departing from the spirit of the present invention.
[0014] (A compound containing lithium sulfate (Li2SO4) and lithium carbonate (Li2CO3)) The oxide solid electrolyte of the present disclosure is a composite containing lithium sulfate (Li2SO4) and lithium carbonate (Li2CO3). Here, the composite refers to a composite obtained by mixing raw materials containing lithium sulfate and lithium carbonate, for example, in a planetary ball mill. By containing lithium sulfate and lithium carbonate, the oxide solid electrolyte of the present disclosure can obtain good electrical conductivity and good deformability.
[0015] (The molar ratio of lithium sulfate to the lithium carbonate (Li2SO4:Li2CO3) is 20:80 to 80:20) The oxide solid electrolyte of the present disclosure contains lithium sulfate (Li2SO4) and lithium carbonate (Li2CO3), and the molar ratio of lithium sulfate to lithium carbonate (Li2SO4:Li2CO3) is 20:80 to 80:20. If the molar ratio of lithium sulfate to lithium carbonate is within the above range, the oxide solid electrolyte has good deformability at room temperature. A more preferable molar ratio of lithium sulfate to lithium carbonate is 30:70 to 70:30.
[0016] In the oxide solid electrolyte of the present disclosure, the total content of lithium sulfate and lithium carbonate is preferably 30% by mass to 100% by mass. If the total content of lithium sulfate and lithium carbonate is within the above range, better deformability at room temperature can be obtained, which is preferable. The total content of lithium sulfate and lithium carbonate is more preferably 40% by mass to 100% by mass.
[0017] (At least one selected from the group consisting of lithium chloride, lithium bromide, lithium iodide, lithium borate, lithium phosphate, lithium nitrate, lithium silicate, and lithium aluminate) The oxide solid electrolyte of the present disclosure preferably further contains at least one selected from the group consisting of lithium chloride, lithium bromide, lithium iodide, lithium borate, lithium phosphate, lithium nitrate, lithium silicate, and lithium aluminate. By further containing at least one selected from the group consisting of lithium chloride, lithium bromide, lithium iodide, lithium borate, lithium phosphate, lithium nitrate, lithium silicate, and lithium aluminate, it is preferable to obtain a higher electrical conductivity.
[0018] The total content of lithium chloride, lithium bromide, lithium iodide, lithium borate, lithium phosphate, lithium nitrate, lithium silicate, and lithium aluminate in the oxide solid electrolyte of the present disclosure is preferably 0% by mass to 70% by mass. If the total content of lithium chloride, lithium bromide, lithium iodide, lithium borate, lithium phosphate, lithium nitrate, lithium silicate, and lithium aluminate is within the above range, better electrical conductivity can be obtained, which is preferable. More preferably, the total content of lithium chloride, lithium bromide, lithium iodide, lithium borate, lithium phosphate, lithium nitrate, lithium silicate, and lithium aluminate is 0% by mass to 60% by mass.
[0019] The chemical composition of the oxide solid electrolyte of the present disclosure can be quantified, for example, by an energy dispersive X-ray spectrometer (EDX) and Raman spectroscopy mounted on a field emission transmission electron microscope (TEM) in a cross section of a positive electrode, a solid electrolyte layer, or a negative electrode of a lithium ion secondary battery.
[0020] (In the curve obtained by differential scanning calorimetry, the heat generation peak is located at 200°C or less.) The oxide solid electrolyte of the present disclosure has an exothermic peak of 200°C or less in a curve (DSC curve) obtained by differential scanning calorimetry (DSC) measurement. When the position of the exothermic peak in the DSC curve is 200°C or less, good deformability of the oxide solid electrolyte can be obtained. A more preferable position of the exothermic peak is 190°C or less. The lower limit of the position of the exothermic peak is not particularly limited, but may be, for example, 80°C or more. When there are multiple exothermic peaks on the DSC curve, the position of the peak with the largest amount of heat generation is regarded as the exothermic peak position.
[0021] The oxide solid electrolyte of the present disclosure preferably has a calorific value of 5 J / g or more at an exothermic peak at 200° C. or less obtained in a DSC curve. If the calorific value of the exothermic peak at 200° C. or less obtained in a DSC curve is within the above range, higher deformability can be obtained, which is preferable. A more preferable calorific value is 10 J / g or more. An even more preferable calorific value is 15 J / g or more. The upper limit of the calorific value of the exothermic peak is not particularly limited, but may be, for example, 500 J / g or less.
[0022] The exothermic peak of the oxide solid electrolyte of the present disclosure can be measured, for example, by the following method. In a glove box filled with an inert gas (e.g., Ar), the oxide solid electrolyte (about 10 mg) is placed in an Al sealed sample container (GCA-0017 manufactured by Hitachi High-Tech Science Corporation) and sealed. The sealed container is placed in a differential scanning calorimeter (e.g., DSC6200 manufactured by Seiko Instruments Inc.) and measurements are performed at a temperature range of 50°C to 300°C and a heating rate of 10°C / min, thereby obtaining a DSC curve of the oxide solid electrolyte. The position of the exothermic peak and the amount of heat generated of the oxide solid electrolyte can be obtained from the obtained DSC curve. The peak position and amount of heat generated can be calculated, for example, using software attached to the differential scanning calorimeter DSC6200.
[0023] (Conductivity is 1.0×10 -7 S / cm or more) The electrical conductivity of the oxide solid electrolyte of the present disclosure is 1.0×10 -7 The electrical conductivity of the oxide solid electrolyte is 1.0×10 S / cm or more. -7 If the conductivity is less than 1.0 S / cm, the characteristics of the all-solid-state lithium-ion battery may be degraded. The more preferable conductivity of the oxide solid electrolyte is 2.0×10 -7 The electrical conductivity of the oxide solid electrolyte is more preferably 4.0×10 -7 S / cm or more.
[0024] The electrical conductivity of the oxide solid electrolyte of the present disclosure can be measured, for example, by the following method. In an argon gas atmosphere glove box, put Al foil or Au foil punched to a diameter of 10 mm into a tablet molder (e.g., manufactured by JASCO) with a diameter of 10 mm, put the solid electrolyte powder on top, and after smoothing, put Al foil or Au foil punched to a diameter of 10 mm again, and press at room temperature and 1 GPa for 30 minutes to obtain pellets for solid electrolyte measurement. The obtained pellets are placed in a flat cell and sealed to make a conductivity measurement cell, and are measured at room temperature with an impedance measurement device (e.g., Solartron Impedance Analyzer A1260) at an applied voltage of 50 mV and a measurement frequency of 1 Hz to 32 MHz, and the conductivity can be calculated from the resistance value of the low-frequency end of the semicircular arc of the obtained Nyquist plot.
[0025] (relative density 95% or more) The oxide solid electrolyte of the present disclosure has excellent deformability at room temperature. For example, when the oxide solid electrolyte of the present disclosure is pressed at 1 GPa at room temperature, the relative density represented by the following formula (1) is 95% or more. More preferably, the relative density when pressed at 1 GPa at room temperature is 98% or more. Even more preferably, the relative density when pressed at 1 GPa at room temperature is 99% or more.
[0026]
number
[0027] The relative density of the oxide solid electrolyte of the present disclosure can be measured by the following method. In an argon gas atmosphere glove box, an Al foil or Au foil punched to a diameter of 10 mm is placed in a tablet molder (e.g., manufactured by JASCO) with a diameter of 10 mm, a solid electrolyte powder is placed on top of it, and after smoothing, an Al foil or Au foil punched to a diameter of 10 mm is further placed, and pressed at room temperature at 1 GPa for 30 minutes to obtain a pellet for relative density measurement. The density of the obtained pellet is calculated by multiplying the density of each raw material (g / cm3) by the above formula (1). 3 ) and mass (g), then divide by the theoretical density.
[0028] The shape of the oxide solid electrolyte of the present disclosure is not particularly limited, but for example, granular shape is preferred.
[0029] (Method of manufacturing oxide solid electrolyte) The method for producing the oxide solid electrolyte of the present disclosure is not particularly limited, and examples thereof include solid phase synthesis, dry mechanical milling, wet mechanical milling, melt quenching, and sol-gel methods. As the method for producing the oxide solid electrolyte of the present disclosure, dry mechanical milling is particularly preferred. For example, the oxide solid electrolyte of the present disclosure can be obtained by mixing the raw material of the oxide solid electrolyte with zirconia balls at 370 rpm for 60 hours. The production conditions can be appropriately adjusted by performing DSC measurement of the obtained oxide solid electrolyte and confirming the position of the heat generation peak and the heat generation amount.
[0030] <Electrode composite material> The electrode mixture of the present disclosure includes the oxide solid electrolyte of the present disclosure, an electrode active material, and a conductive material. The electrode mixture will be described below.
[0031] (active material) The electrode active material is not particularly limited as long as it is used in a lithium ion secondary battery. The electrode active material (positive electrode active material) used in the positive electrode is not particularly limited as long as it is a material that can reversibly release and absorb lithium ions and transport electrons. Examples of the positive electrode active material include lithium transition metal oxides such as lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, and lithium iron phosphate, sulfur and its discharge products such as lithium sulfide and lithium polysulfide, and other sulfur-based active materials. The positive electrode active material may be composed of one type of the above materials alone, or may be composed of two or more types.
[0032] The electrode active material (negative electrode active material) used in the negative electrode is not particularly limited as long as it can reversibly release and absorb lithium ions and transport electrons. Examples of the negative electrode active material include carbonaceous materials such as natural graphite, artificial graphite, resin carbon, carbon fiber, activated carbon, hard carbon, and soft carbon; alloy materials mainly composed of tin, tin alloys, silicon, silicon alloys, gallium, gallium alloys, indium, indium alloys, aluminum, and aluminum alloys; conductive polymers such as polyacene, polyacetylene, and polypyrrole; metallic lithium: lithium titanium composite oxides (e.g., Li4Ti5O 12 The negative electrode active material may be composed of one kind of the above materials alone, or may be composed of two or more kinds of the above materials.
[0033] (Conductive material) The conductive material may be a conductive assistant that can be generally used in lithium ion secondary batteries and all-solid-state lithium ion secondary batteries. Examples of the conductive material used in the positive electrode (positive electrode conductive material) include carbon black such as acetylene black and ketjen black; carbon fiber; vapor-grown carbon fiber; graphite powder; carbon nanotubes, activated carbon, and other carbon materials. The conductive material may be composed of one of the above materials alone, or may be composed of two or more of them.
[0034] Examples of the conductive material used in the negative electrode (negative electrode conductive material) include carbon black such as acetylene black and ketjen black, carbon fiber, vapor grown carbon fiber, graphite powder, carbon nanotubes, activated carbon, and other carbon materials. The conductive material may be composed of one of the above materials alone or two or more of them.
[0035] When the total mass of the oxide solid electrolyte of the present disclosure, the electrode active material, and the conductive material is taken as 100, the mass ratio of the oxide solid electrolyte of the present disclosure, the electrode active material, and the conductive material (oxide solid electrolyte: electrode active material: conductive material) is 20-80: 20-80: 0-30. When the mass ratio of the oxide solid electrolyte of the present disclosure, the electrode active material, and the conductive material is within the above range, high battery characteristics can be obtained. When the oxide solid electrolyte of the present disclosure is used for the positive electrode (positive electrode composite), the mass ratio of the oxide solid electrolyte: the positive electrode active material: the positive electrode conductive material is 20-80: 20-80: 0-30. When the oxide solid electrolyte of the present disclosure is used for the negative electrode (negative electrode composite), the mass ratio of the oxide solid electrolyte: the negative electrode active material: the negative electrode conductive material is 20-80: 20-80: 0-30.
[0036] The content of the oxide solid electrolyte in the electrode mixture of the present disclosure is preferably 20% by mass to 80% by mass. The content of the electrode active material in the electrode mixture of the present disclosure is preferably 20% by mass to 80% by mass. The content of the conductive material in the electrode mixture of the present disclosure is preferably 0% by mass to 30% by mass. More preferably, the content of the conductive material is 0% by mass to 25% by mass. When the contents of the oxide solid electrolyte, the electrode active material, and the conductive material in the electrode mixture of the present disclosure are within the above ranges, good battery characteristics can be obtained. The total of the oxide solid electrolyte, the electrode active material, the conductive material, and other components is 100% by mass. Examples of other components include binders.
[0037] The electrode mixture of the present disclosure may further contain a binder. The binder is not particularly limited, but a thermoplastic resin or a thermosetting resin can be used, for example, polyethylene, polypropylene, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), styrene butadiene rubber, tetrafluoroethylene-hexafluoroethylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-chlorotrifluoroethylene copolymer, ethylene-tetrafluoroethylene copolymer, etc. Polymers (ETFE resins), polychlorotrifluoroethylene (PCTFE), vinylidene fluoride-pentafluoropropylene copolymers, propylene-tetrafluoroethylene copolymers, ethylene-chlorotrifluoroethylene copolymers (ECTFE), vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymers, vinylidene fluoride-perfluoromethylvinyl ether-tetrafluoroethylene copolymers, ethylene-acrylic acid copolymers, polyacrylic acid, sodium polyacrylate, lithium polyacrylate, polymethacrylic acid, sodium polymethacrylate, lithium polymethacrylate, etc. These binders may be used alone or in combination of two or more.
[0038] The binder content in the electrode mixture of the present disclosure is preferably 0% by mass to 10% by mass. Within this range, the active material and the like can be retained while maintaining the electrical conductivity of the electrode mixture. The binder content is more preferably 0% by mass to 5% by mass.
[0039] The ratio of each component in the electrode mixture can be quantified, for example, by an energy dispersive X-ray spectrometer (EDX) mounted on a field emission transmission electron microscope (TEM) in a cross section of the positive or negative electrode of a lithium ion secondary battery, using Raman spectroscopy and a combustion decomposition method.
[0040] (Method of manufacturing electrode mixture) The method for producing the electrode mixture of the present disclosure is not particularly limited as long as the oxide solid electrolyte, the electrode active material, and the conductive material are uniformly mixed. Examples of the method for producing the electrode mixture of the present disclosure include dry mechanical milling, wet mechanical milling, and melt quenching.
[0041] <All-solid-state lithium-ion battery> Next, an all-solid-state lithium-ion battery 100 according to an embodiment of the present disclosure will be described with reference to FIG. 1. The all-solid-state lithium-ion battery 100 includes a solid electrolyte layer 11, a positive electrode composite layer 12, a negative electrode composite layer 13, a positive electrode current collector 14, and a negative electrode current collector 15. The all-solid-state lithium-ion battery 100 includes the oxide solid electrolyte of the present disclosure. That is, the all-solid-state lithium-ion battery 100 includes the oxide solid electrolyte of the present disclosure in at least one of the solid electrolyte layer 11, the positive electrode active material layer 12, and the positive electrode active material layer 13. Each part will be described below.
[0042] (Solid electrolyte layer) The solid electrolyte layer 11 is a layer formed between the positive electrode active material layer 12 and the negative electrode active material layer 13. The solid electrolyte layer 11 contains a solid electrolyte. As the solid electrolyte contained in the solid electrolyte layer 11, a solid electrolyte other than the oxide solid electrolyte of the present disclosure may be used. As the solid electrolyte other than the oxide solid electrolyte of the present disclosure, for example, lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP), lithium lanthanum zirconium oxide (LLZ) and the like can be mentioned. These solid electrolytes may be used alone or in combination of two or more kinds, or may be combined with the oxide solid electrolyte of the present disclosure. The thickness of the solid electrolyte layer 11 can be appropriately selected. The thickness of the solid electrolyte layer 11 is preferably, for example, 200 μm or less.
[0043] The lithium ion conductivity of the solid electrolyte other than the oxide solid electrolyte of the present disclosure is 1.0 × 10 -5 S / cm or more, and more preferably 1.0×10 -4S / cm or more. If the capacitance is in this range, the battery characteristics of the all-solid-state lithium ion battery 100 are further improved.
[0044] The solid electrolyte layer 11 may further contain a binder. The binder is not particularly limited, but a thermoplastic resin, a thermosetting resin, or the like can be used, and examples of the binder include polyethylene, polypropylene, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), styrene butadiene rubber, tetrafluoroethylene-hexafluoroethylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-chlorotrifluoroethylene copolymer, and ethylene-tetrafluoroethylene copolymer. Polymers (ETFE resins), polychlorotrifluoroethylene (PCTFE), vinylidene fluoride-pentafluoropropylene copolymers, propylene-tetrafluoroethylene copolymers, ethylene-chlorotrifluoroethylene copolymers (ECTFE), vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymers, vinylidene fluoride-perfluoromethylvinyl ether-tetrafluoroethylene copolymers, ethylene-acrylic acid copolymers, polyacrylic acid, sodium polyacrylate, lithium polyacrylate, polymethacrylic acid, sodium polymethacrylate, lithium polymethacrylate, etc. These binders may be used alone or in combination of two or more.
[0045] The binder content in solid electrolyte layer 11 of the present disclosure is preferably 0% by mass to 10% by mass. Within this range, the solid electrolyte and the like can be retained while maintaining the conductivity of the electrode mixture. The binder content is more preferably 0% by mass to 5% by mass.
[0046] (Cathode active material layer) The positive electrode active material layer 12 is formed on the positive electrode current collector 14. The positive electrode active material layer 12 includes a solid electrolyte, an electrode active material, and a conductive material. The positive electrode active material layer 12 will be described below. The thickness of the positive electrode active material layer 12 can be appropriately selected. The thickness of the positive electrode active material layer 12 is preferably, for example, 200 μm or less.
[0047] (solid electrolyte) The solid electrolyte contained in the positive electrode active material layer 12 may contain the oxide solid electrolyte of the present disclosure, or may contain a solid electrolyte other than the oxide solid electrolyte of the present disclosure. Examples of solid electrolytes other than the oxide solid electrolyte of the present disclosure include lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP), and lithium lanthanum zirconium oxide (LLZ). The solid electrolytes other than the oxide solid electrolyte of the present disclosure may be used alone or in combination of two or more kinds, or may be combined with the oxide solid electrolyte of the present disclosure.
[0048] The lithium ion conductivity of the solid electrolyte other than the oxide solid electrolyte of the present disclosure is 1.0 × 10 -5 S / cm or more, and more preferably 1.0×10 -4 S / cm or more. If the capacitance is in this range, the battery characteristics of the all-solid-state lithium ion battery 100 are further improved.
[0049] (Cathode active material) The electrode active material (positive electrode active material) used in the positive electrode is not particularly limited as long as it is a material that can reversibly release and absorb lithium ions and transport electrons. Examples of the positive electrode active material include lithium transition metal oxides such as lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, and lithium iron phosphate, and sulfur-based active materials such as lithium sulfide and lithium polysulfide, which are discharge products of sulfur. The positive electrode active material may be composed of one type of the above materials alone, or may be composed of two or more types.
[0050] (Positive electrode conductive material) The positive electrode conductive material may be a conductive assistant that can be generally used in lithium ion secondary batteries and all-solid-state lithium ion secondary batteries. Examples of the positive electrode conductive material include carbon black such as acetylene black and ketjen black; carbon fiber; vapor-grown carbon fiber; graphite powder; carbon nanotubes, activated carbon, and other carbon materials. The conductive material may be composed of one of the above materials alone, or may be composed of two or more of them.
[0051] (Mass ratio of oxide solid electrolyte, positive electrode active material, and positive electrode conductive material: 20-80: 20-80: 0-30) When the positive electrode active material layer 12 contains the oxide solid electrolyte of the present disclosure, the mass ratio of the oxide solid electrolyte of the present disclosure, the positive electrode active material, and the positive electrode conductive material (oxide solid electrolyte: positive electrode active material: positive electrode conductive material) is preferably 20 to 80: 20 to 80: 0 to 30, when the total mass of the oxide solid electrolyte, the positive electrode active material, and the positive electrode conductive material is taken as 100. When the mass ratio of the oxide solid electrolyte of the present disclosure, the positive electrode active material, and the positive electrode conductive material is within the above range, higher battery characteristics can be obtained.
[0052] The content of the oxide solid electrolyte in the positive electrode active material layer 12 is preferably 20% by mass to 80% by mass. The content of the positive electrode active material in the positive electrode active material layer 12 is preferably 20% by mass to 80% by mass. The content of the positive electrode conductive material in the positive electrode active material layer 12 is preferably 0% by mass to 30% by mass. More preferably, the content of the positive electrode conductive material is 0% by mass to 25% by mass. If the contents of the oxide solid electrolyte, the positive electrode active material, and the positive electrode conductive material in the positive electrode active material layer 12 are within the above ranges, better battery characteristics can be obtained. The total of the oxide solid electrolyte, the positive electrode active material, the positive electrode conductive material, and other components is 100% by mass. Examples of other components include a binder.
[0053] The positive electrode active material layer 12 may further contain the binder used in the electrode mixture of the present disclosure.
[0054] (Negative electrode active material layer) The negative electrode active material layer 13 is formed on the negative electrode current collector 15. The negative electrode active material layer 13 includes a solid electrolyte, a negative electrode active material, and a negative electrode conductive material. The negative electrode active material layer 13 will be described below. The thickness of the negative electrode active material layer 13 can be appropriately selected. The thickness of the negative electrode active material layer 13 is preferably, for example, 200 μm or less.
[0055] (solid electrolyte) The solid electrolyte contained in the negative electrode active material layer 13 may contain the oxide solid electrolyte of the present disclosure, or may contain a solid electrolyte other than the oxide solid electrolyte of the present disclosure. Examples of solid electrolytes other than the oxide solid electrolyte of the present disclosure include lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP), and lithium lanthanum zirconium oxide (LLZ). The above solid electrolytes other than the oxide solid electrolyte of the present disclosure may be used alone or in combination of two or more kinds, or may be combined with the oxide solid electrolyte of the present disclosure.
[0056] The lithium ion conductivity of the solid electrolyte other than the oxide solid electrolyte of the present disclosure is 1.0 × 10 -5 S / cm or more, and more preferably 1.0×10 -4 S / cm or more. If the capacitance is in this range, the battery characteristics of the all-solid-state lithium ion battery 100 are further improved.
[0057] (Negative electrode active material) The negative electrode active material is not particularly limited as long as it can reversibly release and absorb lithium ions and transport electrons. Examples of the negative electrode active material include carbonaceous materials such as natural graphite, artificial graphite, resin carbon, carbon fiber, activated carbon, hard carbon, and soft carbon; alloy materials mainly composed of tin, tin alloys, silicon, silicon alloys, gallium, gallium alloys, indium, indium alloys, aluminum, and aluminum alloys; conductive polymers such as polyacene, polyacetylene, and polypyrrole; metallic lithium: lithium titanium composite oxides (e.g., Li4Ti5O 12The negative electrode active material may be composed of one kind of the above materials alone, or may be composed of two or more kinds of the above materials.
[0058] (Negative electrode conductive material) The negative electrode conductive material may be a conductive assistant that can be generally used in lithium ion secondary batteries and all-solid-state lithium ion secondary batteries. The positive electrode conductive material may be, for example, carbon black such as acetylene black and ketjen black; carbon fiber; vapor-grown carbon fiber; graphite powder; carbon nanotubes, activated carbon, and other carbon materials. The conductive material may be composed of one of the above materials alone, or may be composed of two or more of them.
[0059] (Mass ratio of oxide solid electrolyte, negative electrode active material, and negative electrode conductive material: 20-80: 20-80: 0-30) When the negative electrode active material layer 13 contains the oxide solid electrolyte of the present disclosure, the mass ratio of the oxide solid electrolyte of the present disclosure, the negative electrode active material, and the negative electrode conductive material (oxide solid electrolyte:negative electrode active material:negative electrode conductive material) is 20 to 80:20 to 80:0 to 30, when the total mass of the oxide solid electrolyte, the negative electrode active material, and the negative electrode conductive material is taken as 100. When the mass ratio of the oxide solid electrolyte of the present disclosure, the negative electrode active material, and the negative electrode conductive material is within the above range, better battery characteristics can be obtained.
[0060] The content of the oxide solid electrolyte in the negative electrode active material layer 13 is preferably 20% by mass to 80% by mass. The content of the negative electrode active material in the negative electrode active material layer 13 is preferably 20% by mass to 80% by mass. The content of the negative electrode conductive material in the negative electrode active material layer 13 is preferably 0% by mass to 30% by mass. More preferably, the content of the negative electrode conductive material is 0% by mass to 25% by mass. When the contents of the oxide solid electrolyte, the negative electrode active material, and the negative electrode conductive material in the negative electrode active material layer 13 are within the above ranges, better battery characteristics can be obtained. The total of the oxide solid electrolyte, the negative electrode active material, the negative electrode conductive material, and other components is 100% by mass. Examples of other components include a binder.
[0061] The negative electrode active material layer 13 may further contain the binder used in the electrode mixture of the present disclosure.
[0062] (Positive electrode current collector) The positive electrode current collector 14 is provided so as to be in contact with the positive electrode active material layer 12. The presence of the positive electrode current collector 14 makes it easier to extract electricity from the positive electrode active material layer 12. As the positive electrode current collector 14, a known positive electrode current collector can be used, such as Al or SUS. The thickness and shape of the positive electrode current collector 14 can be appropriately selected.
[0063] (Negative electrode current collector) The negative electrode current collector 15 is provided so as to be in contact with the negative electrode active material layer 13. The presence of the negative electrode current collector 15 makes it easier to extract electricity from the negative electrode active material layer 13. As the negative electrode current collector 15, a known negative electrode current collector can be used, for example, Cu. Note that, when the electron conductivity of the negative electrode active material layer 13 is high, the negative electrode current collector 15 does not need to be provided. Also, the thickness and shape of the negative electrode current collector 15 can be appropriately selected.
[0064] The all-solid-state lithium-ion battery 100 can be manufactured by a known method.
[0065] In addition, the components in the above embodiment may be replaced with known components as appropriate without departing from the spirit of the present invention, and the above-mentioned modified examples may be combined as appropriate. In the above embodiment, the positive electrode current collector 14 is provided, but if the electron conductivity of the positive electrode active material layer 12 is high, the positive electrode current collector 14 may not be provided. In the above embodiment, the negative electrode current collector 15 is provided, but if the electron conductivity of the negative electrode active material layer 13 is high, the negative electrode current collector 15 may not be provided. EXAMPLES
[0066] Next, an embodiment of the present invention will be described, but the conditions in the embodiment are merely an example of conditions adopted to confirm the feasibility and effects of the present invention, and the present invention is not limited to this example of conditions. Various conditions can be adopted in the present invention as long as they do not deviate from the gist of the present invention and achieve the object of the present invention.
[0067] Example 1 543 mg of lithium sulfate and 157 mg of lithium carbonate were weighed out so that the molar ratio of lithium sulfate (manufactured by Wako Pure Chemical Industries, Ltd.) and lithium carbonate (manufactured by Rare Metallic Co., Ltd.) was 70:30. Using a planetary ball mill (Premium Line P-7 manufactured by Frillsch), the weighed lithium sulfate and lithium carbonate were placed in an 80 ml pot together with about 120 g of 5 mm zirconia balls, and mixed at a revolution speed of 370 rpm for 60 hours to obtain the oxide solid electrolyte of Example 1.
[0068] Example 2 828 mg of lithium sulfate and 372 mg of lithium carbonate were weighed out so that the molar ratio of lithium sulfate to lithium carbonate was 60:40, and then mixed under the same conditions as in Example 1 to obtain an oxide solid electrolyte of Example 2.
[0069] Example 3 359 mg of lithium sulfate and 241 mg of lithium carbonate were weighed out so that the molar ratio of lithium sulfate and lithium carbonate was 50:50, and then mixed under the same conditions as in Example 1 to obtain an oxide solid electrolyte of Example 3.
[0070] Example 4 299 mg of lithium sulfate and 301 mg of lithium carbonate were weighed out so that the molar ratio of lithium sulfate to lithium carbonate was 40:60, and then mixed under the same conditions as in Example 1 to obtain an oxide solid electrolyte of Example 4.
[0071] Example 5 273 mg of lithium sulfate and 427 mg of lithium carbonate were weighed out so that the molar ratio of lithium sulfate to lithium carbonate was 30:70, and then mixed under the same conditions as in Example 1 to obtain an oxide solid electrolyte of Example 5.
[0072] Example 6 Lithium sulfate, lithium carbonate, and lithium iodide (manufactured by Sigma-Aldrich) were weighed out in an amount of 717 mg of lithium sulfate, 321 mg of lithium carbonate, and 162 mg of lithium iodide so that the molar ratio was 54:36:10, and then mixed under the same conditions as in Example 1 to obtain an oxide solid electrolyte of Example 6.
[0073] Example 7 614 mg of lithium sulfate, 275 mg of lithium carbonate, and 311 mg of lithium iodide were weighed out so that the molar ratio of lithium sulfate, lithium carbonate, and lithium iodide was 48:32:20, and then mixed under the same conditions as in Example 1 to obtain an oxide solid electrolyte of Example 7.
[0074] Example 8 518 mg of lithium sulfate, 232 mg of lithium carbonate, and 450 mg of lithium iodide were weighed out so that the molar ratio of lithium sulfate, lithium carbonate, and lithium iodide was 42:28:30, and then mixed under the same conditions as in Example 1 to obtain an oxide solid electrolyte of Example 8.
[0075] Example 9 428 mg of lithium sulfate, 192 mg of lithium carbonate, and 280 mg of lithium iodide were weighed out so that the molar ratio of lithium sulfate, lithium carbonate, and lithium iodide was 36:24:40, and then mixed under the same conditions as in Example 1 to obtain an oxide solid electrolyte of Example 9.
[0076] Example 10 345 mg of lithium sulfate, 155 mg of lithium carbonate, and 700 mg of lithium iodide were weighed out so that the molar ratio of lithium sulfate, lithium carbonate, and lithium iodide was 30:20:50, and then mixed under the same conditions as in Example 1 to obtain an oxide solid electrolyte of Example 10.
[0077] Example 11 Lithium sulfate, lithium carbonate, and lithium chloride (manufactured by Sigma-Aldrich) were weighed out in an amount of 746 mg of lithium sulfate, 334 mg of lithium carbonate, and 120 mg of lithium chloride so that the molar ratio was 48:32:20, and then mixed under the same conditions as in Example 1 to obtain an oxide solid electrolyte of Example 11.
[0078] Example 12 722 mg of lithium sulfate, 323 mg of lithium carbonate, and 155 mg of lithium chloride were weighed out so that the molar ratio of lithium sulfate, lithium carbonate, and lithium chloride was 45:30:25, and then mixed under the same conditions as in Example 1 to obtain an oxide solid electrolyte of Example 12.
[0079] (Example 13) 696 mg of lithium sulfate, 312 mg of lithium carbonate, and 192 mg of lithium chloride were weighed out so that the molar ratio of lithium sulfate, lithium carbonate, and lithium chloride was 42:28:30, and then mixed under the same conditions as in Example 1 to obtain an oxide solid electrolyte of Example 13.
[0080] Example 14 639 mg of lithium sulfate, 287 mg of lithium carbonate, and 274 mg of lithium chloride were weighed out so that the molar ratio of lithium sulfate, lithium carbonate, and lithium chloride was 36:24:40, and then mixed under the same conditions as in Example 1 to obtain an oxide solid electrolyte of Example 14.
[0081] Example 15 Lithium sulfate, lithium carbonate, and lithium bromide (manufactured by Sigma-Aldrich) were weighed out in an amount of 338 mg of lithium sulfate, 151 mg of lithium carbonate, and 111 mg of lithium bromide so that the molar ratio was 48:32:20, and then mixed under the same conditions as in Example 1 to obtain an oxide solid electrolyte of Example 15.
[0082] Example 16 636 mg of lithium sulfate, 285 mg of lithium carbonate, and 279 mg of lithium bromide were weighed out so that the molar ratio of lithium sulfate, lithium carbonate, and lithium bromide was 45:30:25, and then mixed under the same conditions as in Example 1 to obtain an oxide solid electrolyte of Example 16.
[0083] (Example 17) 596 mg of lithium sulfate, 267 mg of lithium carbonate, and 336 mg of lithium bromide were weighed out so that the molar ratio of lithium sulfate, lithium carbonate, and lithium bromide was 42:28:30, and then mixed under the same conditions as in Example 1 to obtain an oxide solid electrolyte of Example 17.
[0084] (Example 18) 258 mg of lithium sulfate, 116 mg of lithium carbonate, and 226 mg of lithium bromide were weighed out so that the molar ratio of lithium sulfate, lithium carbonate, and lithium bromide was 36:24:40, and then mixed under the same conditions as in Example 1 to obtain an oxide solid electrolyte of Example 18.
[0085] (Example 19) Lithium sulfate, lithium carbonate, and lithium phosphate (manufactured by Sigma-Aldrich) were weighed out in an amount of 530 mg of lithium sulfate, 237 mg of lithium carbonate, and 233 mg of lithium bromide so that the molar ratio of lithium sulfate, lithium carbonate, and lithium phosphate was 48:32:20, and then mixed under the same conditions as in Example 1 to obtain an oxide solid electrolyte of Example 19.
[0086] (Example 20) Lithium sulfate (585 mg), lithium carbonate (262 mg), and lithium bromide (153 mg) were weighed out so that the molar ratio of lithium sulfate, lithium carbonate, and lithium nitrate (manufactured by Sigma-Aldrich) was 48:32:20, and then mixed under the same conditions as in Example 1 to obtain an oxide solid electrolyte of Example 20.
[0087] Comparative Example 1 Lithium borate (manufactured by Toshima Manufacturing Co., Ltd.) and lithium sulfate were weighed out in an amount of 1,040 mg and 160 mg, respectively, so that the molar ratio of lithium borate and lithium sulfate was 90:10. These were then mixed under the same conditions as in Example 1 to obtain a solid electrolyte of Comparative Example 1.
[0088] Comparative Example 2 The solid electrolyte of Comparative Example 1 was heat-treated at 285° C. for 1 hour in an argon atmosphere to obtain a solid electrolyte of Comparative Example 2.
[0089] (Positive electrode mixture 1) Lithium nickel cobalt manganese oxide (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 60 mg of ZnO2 (manufactured by BASF Toda Battery Materials) and 40 mg of the oxide solid electrolyte of Example 2 were weighed out and mixed in an agate mortar to obtain a powdered positive electrode mixture 1.
[0090] (Positive electrode mixture 2) The solid oxide electrolyte of Example 13 was used instead of the solid oxide electrolyte of Example 2, and the materials were weighed and mixed in the same manner as in the positive electrode mixture 1 to obtain a powdered positive electrode mixture 2.
[0091] (Positive electrode mixture 3) As the positive electrode active material, 60 mg of lithium sulfide (manufactured by Mitsuwa Chemical Industry Co., Ltd.), 120 mg of the oxide solid electrolyte of Example 13, and 20 mg of activated carbon (MSC-30) were weighed out. Using a planetary ball mill (Premium Line P-7 manufactured by Frilsch), the lithium sulfide weighed out together with about 40 g of 5 mm zirconia balls, the oxide solid electrolyte of Example 13, and the activated carbon were placed in a 45 ml pot and mixed at a revolution speed of 370 rpm for 2 hours to obtain a powdered positive electrode composite material 3.
[0092] (Positive electrode mixture 4) The powdered positive electrode mixture 4 was obtained by weighing and mixing under the same conditions as those for the positive electrode mixture 3, except that the positive electrode mixture 4 of Example 16 was used instead of the positive electrode mixture 13 of Example 13.
[0093] (Positive electrode mixture 5) As the positive electrode active material, 60 mg of lithium sulfide, 60 mg of the oxide solid electrolyte of Example 13, and 20 mg of activated carbon (MSC-30) were weighed. Using a planetary ball mill (Frilsch Premium Line P-7), the lithium sulfide weighed together with about 40 g of 5 mm zirconia balls, the oxide solid electrolyte of Example 13, and the activated carbon were placed in a 45 ml pot and mixed for 2 hours at a revolution speed of 370 rpm. The obtained powder and the solid electrolyte of Example 13 were weighed to have a mass ratio of 70:30, and mixed in a mortar to obtain a powdered positive electrode mixture 5.
[0094] (Positive electrode mixture 6) The powdered positive electrode mixture 6 was obtained by weighing and mixing under the same conditions as those for the positive electrode mixture 5, except that the oxide solid electrolyte of Example 16 was used instead of the oxide solid electrolyte of Example 13.
[0095] (Comparative positive electrode mixture 1) A comparative positive electrode mixture 1 was obtained by weighing and mixing in the same manner as in the positive electrode mixture 1, except that the solid electrolyte of Comparative Example 2 was used instead of the oxide solid electrolyte of Example 2.
[0096] (Comparative positive electrode mixture 2) A comparative powdered positive electrode composite 2 was obtained by weighing and mixing in the same manner as in the positive electrode composite 1, except that lithium aluminum germanium phosphate (LAGP, manufactured by Toshima Manufacturing Co., Ltd.) was used as the oxide solid electrolyte instead of the solid electrolyte in Example 2.
[0097] (Comparative positive electrode mixture 3) A comparative powdered positive electrode composite 3 was obtained by weighing and mixing in the same manner as in the positive electrode composite 1, except that lithium aluminum titanium phosphate (LATP, manufactured by Toshima Manufacturing Co., Ltd.) was used as the oxide solid electrolyte instead of the solid electrolyte in Example 2.
[0098] (Negative electrode composite material 1) Lithium titanium oxide (Li4Ti5O 12 50 mg of Li-ion Toluene (LTO, manufactured by Ishihara Sangyo Kaisha) and 50 mg of the oxide solid electrolyte of Example 2 were weighed out and mixed in an agate mortar to obtain a powdered negative electrode mixture 1.
[0099] (Negative electrode composite material 2) A powdered negative electrode mixture 2 was obtained by mixing in an agate mortar under the same conditions as for the negative electrode mixture 1, except that 50 mg of the oxide solid electrolyte of Example 8 was weighed out instead of the oxide solid electrolyte of Example 2.
[0100] (Negative electrode composite material 3) 50 mg of graphite (manufactured by Wako Pure Chemical Industries, Ltd.) as the negative electrode active material and 50 mg of the oxide solid electrolyte of Example 13 were weighed out and mixed in an agate mortar to obtain a powdered negative electrode mixture 3.
[0101] (Negative electrode composite material 4) 50 mg of silicon (manufactured by Nikola Corp.) as the negative electrode active material and 50 mg of the oxide solid electrolyte of Example 13 were weighed out and mixed in an agate mortar to obtain a powdered negative electrode mixture 4.
[0102] (Negative electrode composite material 5) The powdered negative electrode mixture 5 was obtained by weighing and mixing in the same manner as in the positive electrode mixture 3, except that silicon was used as the negative electrode active material instead of the lithium sulfide as the positive electrode active material.
[0103] (Negative electrode composite material 6) The powdered negative electrode mixture 6 was obtained by weighing and mixing in the same manner as the positive electrode mixture 5, except that silicon was used as the negative electrode active material instead of the lithium sulfide as the positive electrode active material.
[0104] (Battery making method-1) In an argon gas atmosphere glove box, Al foil or Cu foil punched to a diameter of 10 mm was placed in a tablet molder (JASCO) with a diameter of 10 mm, and the positive electrode composite or negative electrode composite was placed on top of it and pressed with a specified pressure to prepare a positive electrode. Next, the obtained electrode was placed on a SUS plate with a diameter of 15.5 mm, a polyethylene oxide-based polymer solid electrolyte film containing lithium salt was attached on top of it, and a Li metal foil (thickness 0.2 mm) punched to φ12 mm was placed on the opposite side of the positive electrode as a counter electrode. This was sealed to prepare an evaluation battery. Note that Al foil was used for all evaluations of the positive electrode composite, and Al foil was used for the evaluation of the negative electrode composite when it contained LTO, and Cu foil was used for the evaluation of graphite and silicon.
[0105] (Battery making method-2) In an argon gas atmosphere glove box, a cylindrical jig made of SKD11 (10 mmΦ, height 10 mm) was inserted as a negative electrode current collector from the bottom of a ceramic cylindrical tube jig (inner diameter 10 mmΦ, outer diameter 23 mmΦ, height 20 mm), and 80 mg of solid electrolyte (E) (a mixed composite obtained by mixing composite 1 obtained by firing 5Li2S-GeS2-P2S5 at 510 ° C for 8 hours and composite 2 obtained by treating 80Li2S-20P2S5 in a ball mill at 500 rpm for 10 hours in a mass ratio of 90:10) was inserted from the top of the ceramic cylindrical tube jig. Furthermore, a cylindrical jig made of SKD11 (10 mmΦ, height 15 mm) was inserted as a positive electrode current collector from the top of the ceramic cylindrical tube jig to sandwich the solid electrolyte (E), and pressed at a pressure of 80 MPa for 3 minutes to form a solid electrolyte layer with a diameter of 10 mmΦ and a thickness of about 0.6 mm. Next, the cylindrical jig made of SKD11 (positive electrode current collector) that had been inserted from above was temporarily removed, and the positive electrode composite or negative electrode composite prepared was placed on top of the solid electrolyte layer inside the cylindrical ceramic tube. The cylindrical jig made of SKD11 (positive electrode current collector) was then inserted again from above, and pressed at a pressure of 720 MPa for 3 minutes to form a positive electrode layer with a diameter of 10 mmΦ and a thickness of approximately 0.1 mm. Next, the cylindrical jig (negative electrode current collector) made of SKD11 inserted from the bottom was removed, and a 0.20 mm thick lithium sheet (manufactured by Honjo Metals) punched to a diameter of 8 mmΦ with a hole punch as a negative electrode and a 0.3 mm thick indium sheet (manufactured by Furuuchi Chemical Co., Ltd.) punched to a diameter of 9 mmΦ with a hole punch were stacked and inserted from the bottom of a ceramic cylindrical tube jig, and a cylindrical jig (negative electrode current collector) made of SKD11 was inserted from the bottom again, and pressed for 3 minutes at a pressure of 80 MPa to form a lithium-indium alloy negative electrode. In this way, an all-solid-state lithium ion battery was produced in which, from the bottom, a negative electrode current collector, a lithium-indium alloy negative electrode layer, a solid electrolyte layer, a positive electrode layer, and a positive electrode current collector were stacked. This was sealed to form an evaluation battery.
[0106] (Full Cell 1) In an argon gas atmosphere glove box, an Al foil punched to a diameter of 10 mm was placed in a tablet molder (JASCO) with a diameter of 10 mm, and then the powder of the positive electrode composite material 1 was placed on top of it and pressed at 400 MPa to form a positive electrode layer, and then a solid electrolyte powder (a mortar mixture of the solid electrolyte of Comparative Example 2 and the solid electrolyte of Example 3 in a mass ratio of 75:25) was placed on top of it and pressed at 400 MPa, and then the powder of the negative electrode composite material 2 and Al foil were placed on top of it and pressed at 1 GPa to produce a full cell of an all-solid-state lithium ion battery with three layers stacked, a positive electrode layer, a solid electrolyte layer and a negative electrode layer. This was sealed to prepare an evaluation battery.
[0107] (Conductivity measurement of solid electrolyte) In an Ar gas atmosphere glove box, an Al foil or Au foil punched to a diameter of 10 mm was placed in a tablet molder (JAPAN SPECTRAL) with a diameter of 10 mm, and solid electrolyte powder (Examples 1-20, Comparative Examples 1 and 2) was placed on top of it, and after leveling, an Al foil or Au foil punched to a diameter of 10 mm was further placed and pressed at 1 GPa for 30 minutes to obtain pellets for solid electrolyte measurement. This was placed in a flat cell manufactured by Hosen Co., Ltd. and sealed to obtain a cell for measuring conductivity. Next, at room temperature, an impedance measuring device (Solartron Impedance Analyzer A1260) was used to measure at an applied voltage of 100 mV and a measurement frequency of 1 Hz to 32 MHz, and the conductivity was calculated from the resistance value of the low-frequency end of the semicircular arc of the obtained Nyquist plot. Table 1 summarizes the conductivity and relative density of each solid electrolyte.
[0108] (How to calculate relative density) The density of the pellets for solid electrolyte measurement obtained by 1 GPa pressing was divided by the theoretical density calculated from the density of each raw material using the above formula (1). Here, the density (g / cm3) of each raw material was calculated as 2.22 for lithium sulfate, 2.11 for lithium carbonate, 4.08 for lithium iodide, 3.46 for lithium bromide, 2.07 for lithium chloride, 2.16 for lithium borate, 2.54 for lithium phosphate, and 2.38 for lithium nitrate. The results are shown in Table 1. A relative density of 95% or more was considered to pass.
[0109] (Peak heat generation temperature of solid electrolyte) In a glove box filled with Ar gas, the oxide solid electrolytes (about 10 mg) of Examples 1 to 20 and Comparative Examples 1 and 2 were placed in an Al sealed sample container (GCA-0017 manufactured by Hitachi High-Tech Science Corporation) and sealed. The sealed container was placed in a differential scanning calorimeter (e.g., DSC6200 manufactured by Seiko Instruments Inc.) and measurements were performed at a temperature range of 50°C to 300°C and a heating rate of 10°C / min, thereby obtaining a DSC curve of the oxide solid electrolyte. The position of the heat generation peak and the heat generation amount of the oxide solid electrolyte were obtained from the obtained DSC curve. The results are shown in Table 1.
[0110] (Charge-discharge characteristic evaluation of positive and negative electrode mixtures) The above positive electrode mixtures 1 to 6 and comparative positive electrode mixtures 1 to 3 were used to prepare evaluation batteries by the battery preparation method 1 or 2. The evaluation batteries were charged and discharged at a constant current using a charge / discharge device (ACD-M01A, manufactured by Aska Electronics Co., Ltd. or HJ1001SD8, manufactured by Hokuto Denko Co., Ltd.), and the initial discharge capacity or initial charge capacity per electrode active material was measured. The results for the positive electrode mixtures are shown in Table 2. In the case of evaluation of the negative electrode mixtures, evaluation batteries prepared by the battery preparation method 1 or 2 using the negative electrode mixtures 1 to 6 were used. The measurement results for the negative electrode mixtures are shown in Table 3. Here, the charge / discharge characteristics were measured using the discharge capacity for the positive electrode and the charge capacity for the negative electrode. For the batteries using the negative electrode mixtures 5 and 6, the discharge capacity was set to 2500 mAh / g.
[0111] (Full cell charge / discharge characteristic evaluation) The full cell prepared above was charged and discharged at a constant current using a charge / discharge device (ACD-M01A, manufactured by Aska Electronics Co., Ltd. or HJ1001SD8, manufactured by Hokuto Denko Co., Ltd.), and the initial discharge capacity or initial charge capacity per electrode active material was measured. The evaluation results of the full cell are shown in Table 4. Here, the discharge capacity was used as the charge / discharge characteristic for the full cell.
[0112] [Table 1]
[0113] [Table 2]
[0114] [Table 3]
[0115] [Table 4]
[0116] As shown in Table 1, the oxide solid electrolytes of Examples 1 to 20 contained Li2SO4 and Li2CO3, and the molar ratio of Li2SO4 to Li2CO3 was 20:80 to 80:20. The DSC curves had an exothermic peak at 200°C or less, and the relative density of the pellets obtained by pressing at 1 GPa at room temperature was 95% or more. In addition, the oxide solid electrolytes of Examples 1 to 20 had an electrical conductivity of 1.0×10 -7 It was more than S / cm.
[0117] On the other hand, the solid electrolytes of Comparative Examples 1 and 2 did not have an exothermic peak below 200° C. in the DSC curves. Therefore, the relative density of the pellets obtained by pressing at 1 GPa at room temperature was less than 95%, and the deformability at room temperature was poor.
[0118] As shown in Tables 2 to 4, the positive electrode mixtures 1 to 6 using the oxide solid electrolytes of the Examples had superior battery characteristics compared to the comparative positive electrode mixtures 1 to 3. Similarly, the negative electrode mixtures and full cells using the oxide solid electrolytes of the Examples also had superior battery characteristics. [Industrial Applicability]
[0119] By using the oxide solid electrolyte of the present disclosure as the positive electrode, negative electrode, and solid electrolyte layer of an all-solid-state lithium ion battery, it is possible to produce a positive electrode, a negative electrode, and a solid electrolyte layer exhibiting good battery characteristics, as well as a full cell, by simply pressing at room temperature. Since the electrodes and full cells can be formed by a very simple method, the oxide solid electrolyte of the present invention and the electrode mixture using the same are materials suitable for mass production, and therefore have high industrial applicability. [Explanation of symbols]
[0120] 11 solid electrolyte layer, 12 positive electrode active material layer, 13 negative electrode active material layer, 14 positive electrode current collector, 15 negative electrode current collector, 100 all-solid-state lithium-ion battery
Claims
1. Lithium sulfate (Li 2 SO 4 ) and lithium carbonate (Li 2 CO 3 ) The molar ratio of the lithium sulfate to the lithium carbonate (Li 2 SO 4 :Li 2 CO 3 ) is 20:80 to 80:20, In the curve obtained by differential scanning calorimetry, the position of the exothermic peak is 190° C. or less, and the electrical conductivity is 1.0×10 -7 The oxide solid electrolyte has a specific surface area of 1.5 S / cm or more.
2. 2. The oxide solid electrolyte according to claim 1, further comprising at least one selected from the group consisting of lithium chloride, lithium bromide, lithium iodide, lithium borate, lithium phosphate, lithium nitrate, lithium silicate, and lithium aluminate.
3. The oxide solid electrolyte according to claim 1 or 2, An electrode active material; A conductive material; Including, The mass ratio of the oxide solid electrolyte, the electrode active material, and the conductive material (oxide solid electrolyte:electrode active material:conductive material) is 20 to 80:20 to 80:0 to 30.
4. An all-solid-state lithium ion battery comprising the oxide solid electrolyte according to claim 1 or 2.
5. 5. The all-solid-state lithium ion battery according to claim 4, comprising a solid electrolyte layer containing the oxide solid electrolyte.
6. 6. The all-solid-state lithium ion battery according to claim 4, further comprising a positive electrode active material layer containing the oxide solid electrolyte, or a negative electrode active material layer containing the oxide solid electrolyte.
7. 7. The all-solid-state lithium ion battery according to claim 6, wherein the positive electrode active material layer contains the oxide solid electrolyte, a positive electrode active material, and a positive electrode conductive material, and a mass ratio of the oxide solid electrolyte, the positive electrode active material, and the positive electrode conductive material (oxide solid electrolyte:cathode active material:cathode conductive material) is 20-80:20-80:0-30.
8. 8. The all-solid-state lithium ion battery according to claim 6, wherein the negative electrode active material layer contains the oxide solid electrolyte, a negative electrode active material, and a negative electrode conductive material, and a mass ratio of the oxide solid electrolyte, the negative electrode active material, and the negative electrode conductive material (oxide solid electrolyte:negative electrode active material:negative electrode conductive material) is 20-80:20-80:0-30.
Citation Information
Patent Citations
Lithium ion conductive inorganic substance
JP2012246196A
All-solid battery, and manufacturing method thereof
JP2020064701A
Sulfide glass and crystalline solid electrolyte production method, crystalline solid electrolyte, sulfide glass and solid-state battery
WO2016067631A1